Mechanism and structure based design of inhibitors of AMP and adenosine deaminase. (1st August 2021) - Lindell, Stephen D.; Maechling, Simon; Klein, Robert; Freigang, Jörg; Laber, Bernd; Blanazs, Lisa; Leonhardt, Merisa; Haupt, Susanne; Petry, Thomas; Sabina, Richard L.
Graphical abstract: Abstract: Inhibitors of the enzyme adenosine monophosphate deaminase (AMPD) show interesting levels of herbicidal activity. An enzyme mechanism-based approach has been used to design new inhibitors of AMPD starting from nebularine (6 ) and resulting in the synthesis of 2-deoxy isonebularine (16 ). This compound is a potent inhibitor of the related enzyme adenosine deaminase (ADA; IC50 16 nM), binding over 5000 times more strongly than nebularine. It is proposed that the herbicidal activity of compound 16 is due to 5́-phosphorylation in planta to give an inhibitor of AMPD. Subsequently, an enzyme structure-based approach was used to design new non-ribosyl AMPD inhibitors. The initial lead structure was discovered by in silico screening of a virtual library against plant AMPD. In a second step, binding to AMPD was further optimised via more detailed molecular modeling leading to 2-(benzyloxy)-5-(imidazo[2, 1-f][1, 2, 4]triazin-7-yl)benzoic acid (36 ) (IC50 300 nM). This compound does not inhibit ADA and shows excellent selectivity for plant over human AMPD.